2012
DOI: 10.1111/asj.12000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 25‐hydroxy‐cholecalciferol on the development of osteochondrosis in swine

Abstract: The principal objective of this experiment was to evaluate the effect of 25-hydroxy-cholecalciferol (25-OH-D3 ) on the development of osteochondrosis in 6- to 110-kg castrated male pigs. The growth rate and serum calcium and inorganic phosphate levels neither increased nor decreased in response to supplementation of 25-OH-D3 . However, supplemental 25-OH-D3 significantly increased serum levels of 25-OH-D3 and 1α,25-hydroxy-cholecalciferol without any influence on bone mineral density. The 25-OH-D3 -treated gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…In the current study, intakes of 25‐OH‐D 3 had no significant effects on any measurements of bone mineralization, size or strength. This is in agreement with other studies (O'Doherty et al., ; Sugiyama, et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the current study, intakes of 25‐OH‐D 3 had no significant effects on any measurements of bone mineralization, size or strength. This is in agreement with other studies (O'Doherty et al., ; Sugiyama, et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…In commercial swine units, rickets and poor bone formation is reappearing (Dittmer and Thompson, ; Madson, ; Potter, ), which could be an indication of inadequate vitamin D 3 supply. In this respect, supplementation of pig diets with 25‐OH‐D 3 tended to promote normal endochondral ossification, to inhibit osteochondrosis progression and possibly to regenerate destroyed cartilage tissue (Sugiyama et al, ). In the current study, intakes of 25‐OH‐D 3 had no significant effects on any measurements of bone mineralization, size or strength.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, supplementation of 50 μg kg −1 25(OH)D 3 in piglet diets easily reached a blood level of 25(OH)D at 30 ng ml −1 . This conclusion was obtained from previous studies (Witschi et al, 2011;Sugiyama et al, 2013;Regassa et al, 2015;Flohr et al, 2016b;von Rosenberg et al, 2016;Duffy et al, 2018aDuffy et al, , 2018b. According to previous surveys of serum concentrations of 25(OH)D 3 in different growth stages of pigs, it was suggested that an adequate 25(OH)D level for keeping healthy probably exceeds 30 ng ml −1 in serum.…”
Section: Assessment Of Vitamin D Status and Pig Healthmentioning
confidence: 65%
“…In this context, the only study evaluating the role of vitamin D in the osteochondrosis was performed on a swine model. The authors suggested that the dietary supplementation of 25(OH)D can reduce the development of this condition in pigs through VDR activity enhancement, and speculated that the hormone can reduce the IL-1β and TNF-α and promote TGF-β and IGF-1 release, favoring the cartilage homeostasis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%